Is the cost of the new home dialysis techniques still advantageous compared to in-center hemodialysis? An Italian single center analysis and comparison with experiences from western countries - Iadarola, Gian Maria; Giorda, Elisa; Borca, Marco; Morero, Daniela; Sciascia, Savino; Roccatello, Dario (Frontiers in Medicine, 2024)
Introduction Potential advantages of home dialysis remained a questionable issue. Three main factors have to be considered: the progressive reduction in the cost of consumables for in-Center hemodialysis (IC-HD), the widespread use of incremental Peritoneal Dialysis (PD), and the renewed interest in home hemodialysis (H-HD) in the pandemic era. Registries data on prevalence of dialysis modalities generally report widespread underemployment of home dialysis despite PD and H-HD could potentially provide clinical benefits, improve quality of life, and contrast the diffusion of new infection among immunocompromised patients. Methods We examined the economic impact of home dialysis by comparing the direct and indirect costs of PD (53 patients), H-HD (21 patients) and IC-HD (180 patients) in a single hospital of North-west Italy. In order to achieve comparable weekly costs, the average weekly frequency of dialysis sessions based on the dialysis modality was calculated, the cost of individual sessions per patient per week normalized, and the monthly and yearly costs were derived. Results As expected, PD resulted the least expensive procedure (€ 23,314.79 per patient per year), but, notably, H-HD has a lower average cost than IC-HD (€ 35,535.00 vs. € 40,798.98). A cost analysis of the different dialysis procedures confirms the lower cost of PD, especially continuous ambulatory PD, compared to any extracorporeal technique. Discussion Among the hemodialysis techniques, home bicarbonate HD showed the lowest costs, while the weekly cost of Frequent Home Hemodialysis was found to be comparable to In-Center Bicarbonate Hemodialysis.